The Influence of Boarding School Culture and Self-Efficacy on the Job Satisfaction of Honorary Teachers - Rusly, Muhammad; Harapan, Edi; Indrawati, Sri Wahyu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to describe the influence of boarding school culture and self-efficacy, both partially and simultaneously, on the job satisfaction of honorary teachers using a quantitative method. It involves 89 honorary teacher respondents from boarding school in the SU II district of Palembang city. Data were collected through questionnaires and documentation, then analyzed using simple and multiple linear regression techniques. The results show that, partially, boarding school culture has an influence of 99.7% and self-efficacy has an influence of 99.1%. Meanwhile, simultaneously, boarding school culture and self-efficacy have an influence of 99.7% on the job satisfaction of honorary teachers. This study is still limited to the boarding school environment, with most previous studies focusing partially on more general contexts. These findings offer a new contribution by simultaneously considering both variables, indicating the importance of strengthening boarding school culture and empowering self-efficacy to improve the well-being of honorary teachers, which can influence the quality of education.